2023
DOI: 10.3389/fenvs.2023.1020331
|View full text |Cite
|
Sign up to set email alerts
|

Impact of land use and land cover change on the landscape pattern and service value of the village ecosystem in the karst desertification control

Abstract: Human activities have had a significant impact on ecosystems. Studying landscape patterns and ecosystem services (ES) at the village scale based on land use and land cover (LULC) is essential in addressing current ecosystem issues. Based on GF images, the paper selects village ecosystems of karst desertification control (KDC) as the research object. It uses the landscape pattern index, topographic position index (TPI), and value equivalent method to conduct a spatial and temporal analysis of the ecosystem serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 69 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…Planting large numbers of trees in non-forested areas might also not contribute to climate change mitigation [103]. Single-purpose land use and unrealistic land use policies often upset the balance between ecosystem services [5], resulting in reduced overall services [15]. Spatially oriented land use policies can serve to enhance the value of ecosystem services [5].…”
Section: Management Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Planting large numbers of trees in non-forested areas might also not contribute to climate change mitigation [103]. Single-purpose land use and unrealistic land use policies often upset the balance between ecosystem services [5], resulting in reduced overall services [15]. Spatially oriented land use policies can serve to enhance the value of ecosystem services [5].…”
Section: Management Implicationsmentioning
confidence: 99%
“…However, the majority of previous studies focused on non-karst regions or karst areas. Even though a few studies have focused on both areas, they were limited to a specific province [13] or city and county level [15]. The overall characteristics of ecosystem service functions in Southwest China remain unclear [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lu et al (2022) reported that fully decertified lands were evaluated to have a higher ESV than those subjected to partly rocky lands [45]. High elevation (~1100 m) resulted in a higher ESV in provision ESs compared to lower altitude (~800 m) [45], but the ESV for ECSs increased, with rising elevation dominating the topographical index [46]. The evaluation instrument in these studies varied with low matching comparations and, furthermore, the rationality for contrasting ESV needs to be judged by a third-party parameter that has reasonable scientific meaning.…”
Section: Introductionmentioning
confidence: 99%